Penerapan Model Pembelajaran Inkuiri untuk Meningkatkan Pemecahan Masalah dalam Pembelajaran IPA SMP - Selamet Jaya Hia; Agnes Renostini Harefa; Desman Telaumbanua; Toroziduhu Waruwu (Departement of Mathematics Education, 2024)
The research was motivated by the low ability of students to solve science learning problems and the methods used by teachers in the learning process did not vary. This research aims to (1) describe the learning process using the inquiry learning model, (2) describe the quality of the learning process using the inquiry learning model, (3) describe students' problem solving abilities using the inquiry learning model. The research location is UPTD SMP Negeri 8 Gunungsitoli. The research subjects were 32 class IX students. The type of research used is Classroom Action Research which consists of four stages, namely a) Planning, b) Action, c) Observation, and d) Reflection. The research instruments are: a) Observation sheet, b) Problem solving ability test, c) Learning process quality questionnaire, d) Documentation and e) Interview guide sheet. Research results: (1) The science learning process in Cycle I was 71.15% in the sufficient category and in Cycle II it was 87.98% in the very good category. (2) The quality of the science learning process in Cycle I was 71% in the sufficient category and in Cycle II it was 87% in the very high category. (3) Problem-solving ability indicator identified problems by 85% increased to 100%, indicator collected data by 76% increased to 97%, indicator set hypothesis by 70% increased to ie 84%, indicator tested hypothesis by 64% increased to 74%, indicator drew conclusions by 66% increased to 75%, In Cycle I the average value was 70.99 (sufficient), standard deviation was 10.3, in cycle II increased to 85.93 (good), standard deviation 9,1.